Complete chloroplast genome sequence of Parnassia palustris (Celastraceae). Issue 1 (2nd January 2019) - Yu, Huiying; Guo, Feiyi; Liu, Dong; Zhang, Zhixiang
Abstract: The complete chloroplast genome (cp) of Parnassia palustris was reported in this study. The cp genome was 148, 700 bp in length including two inverted repeats (IRs) of 25, 892 bp, which were separated by large single-copy (LSC) and small single-copy (SSC) of 82, 175 and 14, 741 bp, respectively. The GC content was 37%. The genome encoded 124 functional genes, including 78 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Using the whole chloroplast genome sequences alignment of 8 species from Celastraceae, Oxalidaceae, and Malpighiaceae, the phylogenetic relationship was built. The phylogenetic position of P. palustris was consistent with APG IV. The plastid genome of P. palustris will be useful for developing markers for further studies on resolving the relationship within the genus.